Research Status of Clustered Regulary Interspaced Short Palindromic Repeats Technology in the Treatment of Human Papillomavirus (HPV) Infection Related Diseases - Minxue Tang MD (Cancer Control)
Background: CRISPR/Cas9 technology has rapidly advanced as a pivotal tool in cancer research, particularly in the precision targeting required for both detecting and treating malignancies. Its high specificity and low off-target effects make it exceptionally effective in applications involving Human Papillomavirus (HPV) related diseases, most notably cervical cancer. This approach offers a refined methodology for the rapid detection of viral infections and provides a robust platform for the safe and effective treatment of diseases associated with viral infections through gene therapy. Purpose: Gene therapy, within this context, involves the strategic delivery of genetic material into target cells via a vector. This is followed by the meticulous modulation of gene expression, whether through correction, addition, or suppression, specifically honed to target tumor cells while sparing healthy cells. This dual capacity to diagnose and treat at such a precise level underscores the transformative potential of CRISPR/Cas9 in contemporary medical science, particularly in oncology and virology. Research Design: This article provides an overview of the advancements made in utilizing the CRISPR-Cas9 system as a research tool for HPV-related treatments while summarizing its application status in basic research, diagnosis, and treatment of HPV. Data Collection: Furthermore, it discusses the future prospects for this technology within emerging areas of HPV research and precision medicine in clinical practice, while highlighting technical challenges and potential directions for future development.